2021
DOI: 10.1111/tri.13872
|View full text |Cite
|
Sign up to set email alerts
|

Short‐ and long‐term results of liver transplantation according to age at transplant: a single‐center experience of 351 children

Abstract: Pediatric liver transplantation (PLT) has very good results at experienced transplant centers. However, there is still an ongoing discussion about inferior outcomes, especially in young infants. The aim of this retrospective study was to evaluate outcomes of infants compared to older recipients in a single center over 20 years. We conducted a retrospective study of children who received liver transplants at our center between 1991 and 2011. Only patients without other limiting organ involvement were included a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…11 23 Infants are at greatest risk to die while waiting for a suitable organ, with deaths on the waiting list being significantly higher in children under 1 year of age. 7 Additionally, this age group is more likely to suffer from perioperative complications than older children when undergoing LT. 11 24 In pediatric patients listed for acute-on-chronic liver failure (ACLF), the waiting list mortality within 90 days is greater (46.6%) than for other types of failure (< 30%), which is especially concerning to children with BA as they represent a substantial part of patients listed for ACLF (45%). 25 Age and body weight as well as nutrition status have been identified as important factors influencing the outcome of LT in children, 26 stressing the potential of KPE to improve the conditions for LT in BA patients by allowing children to gain weight and recuperate.…”
Section: Discussionmentioning
confidence: 99%
“…11 23 Infants are at greatest risk to die while waiting for a suitable organ, with deaths on the waiting list being significantly higher in children under 1 year of age. 7 Additionally, this age group is more likely to suffer from perioperative complications than older children when undergoing LT. 11 24 In pediatric patients listed for acute-on-chronic liver failure (ACLF), the waiting list mortality within 90 days is greater (46.6%) than for other types of failure (< 30%), which is especially concerning to children with BA as they represent a substantial part of patients listed for ACLF (45%). 25 Age and body weight as well as nutrition status have been identified as important factors influencing the outcome of LT in children, 26 stressing the potential of KPE to improve the conditions for LT in BA patients by allowing children to gain weight and recuperate.…”
Section: Discussionmentioning
confidence: 99%
“…23 . In general, outcomes after LT in pediatric patients are superior to adults, independent of donor or indication for transplantation, reaching 1-year survival rates of up to 95% 34 . Adults undergoing LT for malignant tumors, have unsatisfactory outcomes, in part due to tumor recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…SIOPEL-1 and the World Experience Review showed superior survival rates of 85% at 10 years and 82% at 10 years after primary transplantation [ 22 , 23 ]. Zsiros et al showed in the SIOPEL-3 and-4 studies that transplantation was associated with a 75% 3-year survival rate [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%